One mile under : a Ty Hauck novel - Gross, Andrew, 1952- (William Morrow, an imprint of HarperCollinsPublishers, 2015)
"A pulse-pounding thriller from New York Times bestselling author Andrew Gross, about a whitewater rafting guide who investigates a suspicious death and uncovers a multinational conspiracy"--